The Use of Social Networking Sites in Job Related Activities: A Cross-cultural Comparison - Małgorzata Bartosik-Purgat; Barbara Jankowska (Entrepreneurial Business and Economics Review, 2017)
Objective: The main objective of the paper is to identify the use of Social Networking Sites (SNSs) in job related activities and indicate the interdependencies between these activities and age, gender, as well as education in culturally diversified markets (China, Poland, Turkey, the United States).